Turkic games in the monument «Diwani lugat-it Turk» by M. Kashgari and their significance in the culture of the Turkic peoples - Bastamitova, А.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The monument «Diwani Lugat at-Turk» M. Kashgari is a unique text that reveals the rich culture and language of the medieval Turks. The game is an important part of the culture, spiritual and practical activities of the Turkic people. The article is devoted to the analysis of the and the text of the monument, the author of the article explores equestrian and children’s games that were popular in the medieval era and have continuity with the modern games of the Turkic people. The significance of the article is shown in the fact that for the author through various language units identifies the main structural components of equestrian and children’s games, carries out language and historical and cultural analysis of games captured in the monument. These games include Shogen (Polo), zhambi ATU (archery), horse racing, games in asychki, games in nuts, hide and seek, games with animal horns. The last children’s game is a cultural definition of the monument, as it is characteristic only for that time.